Sintering and characterization of calcium alumino-titanate-SiC composite refractory fired in reducing and oxidizing atmospheres. Issue 15 (15th October 2019) - Chen, Huizi; Chen, Jianwei; Zhao, Huizhong; Yu, Jun; Zhao, Pengda; Wang, Xianghui; Zhang, Han
Abstract: Calcium alumino-titanate (CAT) is characterized by low thermal conductivity, low thermal expansion coefficient, and high refractoriness. The phase changes and microstructural evolution of a CAT-SiC composite refractory are investigated using X-ray diffraction, scanning electron microscopy, and thermodynamic analysis. Results show that the cold crush strengths of specimens fired in an oxidizing atmosphere are higher than those of specimens fired in a reducing atmosphere. In a reducing atmosphere, composites with SiO2 addition fired at 1350 °C exhibited the highest strengths. Good bonding occurred between different local reaction zones in specimens fired in an oxidizing atmosphere compared to those fired in a reducing atmosphere. Furthermore, a coexistent state of CA6 and corundum in CAT is observed in specimens fired in a reducing atmosphere, and mullite whisker growth occurred for composites without AlF3 ·3H2 O addition, where the TiO2 present in CAT acts as a catalyst.